ANALISIS PERHITUNGAN DAN PENERAPAN PAJAK PENGHASILAN PASAL 21 SERTA PELAPORANNYA - Mutiara Dewi; Rizkika Zalzabila Utami; Siti Aisyah; Dini Vientiany (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
PPh Article 21 regulates income tax deductions on income received or earned by domestic individual taxpayers in connection with work, services and other activities. This research aims to analyze the mechanism for withholding, reporting and remitting PPh Article 21 and its implications for employers and employees. The research method used is descriptive analytical with a qualitative and quantitative approach. The research results show that withholding PPh Article 21 makes a significant contribution to state tax revenues, but there are still challenges in implementation caused by taxpayers' lack of understanding and inaccuracies in calculations. This research also provides recommendations for increasing compliance and efficiency in the administration of Income Tax Article 21.